2017
DOI: 10.1002/pros.23379
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic sensitivity of Tc-99m HYNIC PSMA SPECT/CT in prostate carcinoma: A comparative analysis with Ga-68 PSMA PET/CT

Abstract: Tc-99m HYNIC PSMA may be a useful in imaging of prostate cancer although with a lower sensitivity for lesion detection compared to Ga-68 PSMA PET/CT. Its use is recommended when Ga-68 PSMA is not readily available, in planning radio-guided surgery or the patient is being considered for radio-ligand therapy with Lu-177 PSMA. It performs poorly in detecting small-sized lesions hence its use is not recommended in patients with small volume disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…Patients were considered suitable for treatment if metastatic lesions identified demonstrated sufficient expression of the PSMA defined as uptake greater than twice the physiologic uptake in the normal liver. Synthesis of 68 Ga-PSMA-11 and the performance of PET/CT imaging were as we have previously reported [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…Patients were considered suitable for treatment if metastatic lesions identified demonstrated sufficient expression of the PSMA defined as uptake greater than twice the physiologic uptake in the normal liver. Synthesis of 68 Ga-PSMA-11 and the performance of PET/CT imaging were as we have previously reported [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the similar sensitivity and specificity found with PSMA PET/CT were derived from patients with clinically more challenging conditions. The specificity of SPECT imaging in our cohort with a high tumor burden seems to be overestimated, especially because recently published data indicated the superiority of 68 Ga-PSMA PET/CT over 99m Tc-PSMA SPECT/CT, particularly in patients with low-volume disease or PSA relapse (33,34).…”
Section: Discussionmentioning
confidence: 73%
“…This might be due to the increased importance of PET's higher spatial resolution compared to SPECT when evaluating comparably small lesions associated with low PSA levels. In a relevant recent study, Lawal et al compared PSMA targeting SPECT ( 99m Tc‐HYNIC‐iPSMA) and PET ( 68 Ga‐PSMA‐HBED‐CC) ligands in the same 19 patients and found lower detection rates for the SPECT tracer. They found that the lesions size was a strong predictor of lesion detection in SPECT.…”
Section: Discussionmentioning
confidence: 99%